In Situ Hybridization for Molecular Detection of Human Papilloma Viral 6 / 11 DNA in Adenoctomized Tissues from A group of Iraqi Pediatric Patients (Baghdad Science Journal, 2022)
Among more than 200 different human papilloma viral genotypes, the association of low oncogenic risk-HPV genotypes have been recognized with a variety of oral, oropharyngeal, nasopharyngeal benign tumors as well as non-neoplastic polyposis and papillomas and adenoid hypertrophy. This prospective case- control study aims to determine the rate of DNA detection of HPV genotype 6/11 in nasopharyngeal adeno- tonsillar tissues from a group of patients subjected to adenoctomy for adenoid hypertrophy . A total number of nasopharyngeal adeno-tonsillar tissue specimens from pediatric patients with adenoid hypertrophy were enrolled; 40 nasopharyngeal adeno-tonsillar tissues from patients with adenoid hypertrophy, and 20 normal nasal tissue specimens were obtained from pediatric patients following trimming operations of their inferior nasal turbinates' with unremarkable pathological changes (as an apparently healthy control group). The molecular detection methods for HPV detection were performed by using DNA probes via a recent version of chromogenic in situ hybridization specified for low- risk HPV genotypes.  Among total adenoid hypertrophied tissue specimens group, 8 out of 40 were found to contain positive results for DNA of HPV 6 / 11 genotype, constituting 20% of the total screened nasopharyngeal adenotonsillar tissues. No positive– CISH reactions were detected in the control nasal tissues. The statistical analysis of results in this research showed significant difference when compared to the control apparently healthy tissues.   The significant rate of low- oncogenic HPV genotypes detection in those adenoid hypertrophied tissues could play, in part, a role in their pathogenesis and / or constituting a herald focus for the spread of such important virally transmitted infection.